Transitional Adsorption and Partition of Nonpolar and Polar Aromatic Contaminants by Biochars of Pine Needles with Different Pyrolytic Temperatures - Chen, Baoliang; Zhou, Dandan; Zhu, Lizhong (Environmental science & technology, 2008)
The combined adsorption and partition effects of biochars with varying fractions of noncarbonized organic matter have not been clearly defined. Biochars, produced by pyrolysis of pine needles at different temperatures (100−700 °C, referred as P100−P700), were characterized by elemental analysis, BET-N2 surface areas and FTIR. Sorption isotherms of naphthalene, nitrobenzene, and m-dinitrobenzene from water to the biochars were compared. Sorption parameters (N and logK f) are linearly related to sorbent aromaticities, which increase with the pyrolytic temperature. Sorption mechanisms of biochars are evolved from partitioning-dominant at low pyrolytic temperatures to adsorption-dominant at higher pyrolytic temperatures. The quantitative contributions of adsorption and partition are determined by the relative carbonized and noncarbonized fractions and their surface and bulk properties. The partition of P100−P300 biochars originates from an amorphous aliphatic fraction, which is enhanced with a reduction of the substrate polarity; for P400−P600, the partition occurs with a condensed aromatic core that diminishes with a further reduction of the polarity. Simultaneously, the adsorption component exhibits a transition from a polarity-selective (P200−P400) to a porosity-selective (P500−P600) process, and displays no selectivity with P700 and AC in which the adsorptive saturation capacities are comparable to predicted values based on the monolayer surface coverage of molecule.